String along with researchers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Dimensions of Participation Experiences, Lessons and Tips from Agricultural Research Practitioners in Sub-Saharan Africa By A Sutherland, A Martin and D Rider Smith, Natural Resources Institute and Department for International Development, 2001. 328 pp.